EFFECTIVE USE OF CRITICAL THINKING TECHNOLOGY IN TEACHING FICTION AT THE UNIVERSITY - Karlygash Abildayeva, (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This article systematically examines the issue of the effective use of critical thinking in teaching students fiction. According to the technology of developing critical thinking, the work of researchers is first reviewed and the significance of this technology is determined on the basis of their opinions. From several methods, strategies of critical thinking that activate students in the classroom, those that are inherent in the nature of the work are selected. From several methods, strategies of critical thinking that activate students in the classroom, those that are inherent in the nature of the work are selected. They are sorted into three stages of critical thinking development technology. An example is taken by Miguel de Cervantes’ novel Don Quixote, which studies the effectiveness of approaches to the complete assimilation of new material by students. The problem of forming a creative person who can critically analyze the fate of the main characters in the work with modern life was also mentioned. It is revealed that the system of tasks given to students leads to success in awakening cognitive activity, understanding new information, discussing and systematizing.